Doświadczenia zawodowe osób rozpoczynających studia na kierunkach społecznych Uniwersytetu Zielonogórskiego w kontekście niedopasowania behawioralnego = Professional experience of people beginning social studies at the University of Zielona Gora in the context of behavioural maladjustment - Nyćkowiak, Justyna; Kołodziej, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt to answer the question of the extent to which people making the choice of studies take into account the real situation on the labour market and its changes. Presented analyses try to determine the level of behavioural maladjustment understood as inability of applying action strategies which are adequate to the situation on the labour market. It is assumed that the students with prior professional experience were willing to make a choice of studies based on different criteria than the students with no experience.
Keywords: labour market; professional experience; behavioural maladjustment; rynek pracy; doświadczenie zawodowe; niedostosowanie behawioralne